Anticardiolipin Antibodies Block the Inhibition by β2-Glycoprotein I of the Factor Xa Generating Activity of Platelets - Shi, Wei; Chong, Beng H; Hogg, Philip J; Chesterman, Colin N (Thrombosis and Haemostasis, 1993)
Antiphospholipid antibodies, defined either by lupus anticoagulant (LA) activity or positive anticardiolipin immunoabsorbent assay (ACA) are associated with a predisposition to thromboses, recurrent fetal loss or thrombocytopenia. The mechanisms for these predispositions remain undefined. We have enriched immunoglobulin fractions from two patient plasmas to obtain antibodies with LA activity but no ACA, or conversely, with ACA positivity but no LA, in order to investigate in vitro characteristics which might explain a thrombotic propensity. β2-glycoprotein I (β2-GPI), the plasma cofactor required for ACA binding to negatively charged phospholipid, has previously been shown to inhibit prothrombinase generation in the presence of activated platelets (8). We now report that β2-GPI, at physiological concentrations, inhibits the generation of factor Xa in the presence of activated gel-filtered platelets. Further, ACA interferes with this inhibition, resulting in protracted, unopposed factor Xa generation. This interference with β2-GPI, a natural anticoagulant component of plasma, is potentially prothrombotic. LA immunoglobulins behave differently and inhibit factor Xa generation in a manner similar to β2-GPI. These findings provide the basis for a previously unsuspected mechanism for thrombosis in patients with aPL.